STUDENTS’ ATTITUDES AND PROBLEMS ON QUESTION-BASED ARGUMENTATIVE ESSAY WRITING INSTRUCTION - Wubante Mekonnen Seyoum; Abiy Yigzaw; Haile Kassahun Bewuketu (Journal of English Language Teaching and Learning, 2022)
Teaching argumentative essay writing to students through questioning is prominent to provide them with sufficient skills to compete in this world. Having this in mind, this descriptive study was conducted to identify students’ attitudes and their common problems in practicing argumentative essay writing skills through questioning method at DMU, in Ethiopia. To fulfill the purpose of this study, sixty management students answered the questionnaire. The results from the questionnaire revealed that all students have positive attitudes towards using the method while practicing writing. The data also revealed that inappropriate teaching method, time constraints, and large class size were the most common problems that did not allow students to apply their argumentative essay writing skills through questioning method effectively. This study recommends educators, policymakers, and  other stakeholders to reconsider the attitudes and problems of university students while designing question-based argumentative essay writing teaching materials.